Production of 1‐Octanol from n‐Octane by Pseudomonas putida KT2440. Issue 6 (25th April 2013) - Vallon, Tobias; Glemser, Matthias; Malca, Sumire Honda; Scheps, Daniel; Schmid, Joachim; Siemann‐Herzberg, Martin; Hauer, Bernhard; Takors, Ralf
Abstract A two‐phase biotransformation process for selective hydroxylation of n‐octane to 1‐octanol via Pseudomonas putida KT2440 harboring heterologously expressed P450 monooxygenase from Mycobacterium marinum is presented. Maximum cell‐specific conversion rates of 12.7 mgoctanol gCDWh–1 were observed not only in shaking flasks but also in 3.7‐L‐bioreactor studies. The bioreactor experiments were performed avoiding explosive gas mixtures by lowering volumetric power input, aeration rates and substrate concentrations. Based on a stoichiometric network of P. putida KT2440 topological studies were carried out. As a conclusion, potential limitations of NAD(P)H and/or ATP supply at production conditions can be excluded. Hence, the great potential of the host for further increasing conversion is outlined.